已知函数f(x)=x-
(I)设f′(x)=
(II)证明:0<an+1<an≤1; (III)记Tn=
|
(I)∵f′(x)=
,f′(x)=(1+x)2-1+ln(1+x) (1+x)2
,g(x) (1+x)2
∴g(x)=(1+x)2-1+ln(1+x)
∴g′(x)=2(1+x)+1 1+x
当x≥0时,g′(x)>0,∴g(x)在[0,+∞)上为增函数,
∴g(x)≥g(0)=0,即g(x)的最小值为0;
(II)证明:①当n=1时,a2=f(a1)=a1-
<a1=1,ln(1+a1) 1+a1
又g(x)≥0,则f′(x)=
≥0g(x) (1+x)2
所以f(x)在[0,+∞)上为增函数,即f(x)≥f(0)=0
则a2=f(a1)>f(0)=0,所以0<a2<a1≤1;
②假设当n=k时,结论成立,即0<ak+1<ak≤1,则
当n=k+1时,ak+2=f(ak+1)=ak+1-
<ak+1≤1ln(1+ak+1) 1+ak+1
∵f(x)在[0,+∞)上为增函数,
∴ak+2=f(ak+1)>f(0)=0
∴0<ak+2<ak+1≤1,
∴当n=k+1时,结论也成立.
由①②知,0<an+1<an≤1;
(III)证明:由(II)0<an+1<an≤1得
>1 an+1
,即1+1 an
>1+1 an+1 1 an
故
<an+1 1+an+1 an 1+an
则Tn=
+an 1+a1
+…+a1a2 (1+a1)(1+a2) a1a2…an (1+a1)(1+a2)…(1+an)
<
+(a1 1+a1
)2+…+(a1 1+a1
)n=a1 1+a1
<
[1-(a1 1+a1
)n]a1 1+a1 1- a1 1+a1
=a1=1a1 1+a1 1+ a1 1+a1
所以Tn<1成立.